2021
DOI: 10.1038/s41541-021-00365-w
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of MERS coronavirus through a scalable nanoparticle vaccine

Abstract: MERS-CoV continues to cause human outbreaks, so far in 27 countries worldwide following the first registered epidemic in Saudi Arabia in 2012. In this study, we produced a nanovaccine based on virus-like particles (VLPs). VLPs are safe vaccine platforms as they lack any replication-competent genetic material, and are used since many years against hepatitis B virus (HBV), hepatitis E virus (HEV) and human papilloma virus (HPV). In order to produce a vaccine that is readily scalable, we genetically fused the rec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Using this technique, we have recently developed a vaccine against MERS‐CoV by incorporating the RBM of MERS‐CoV into CuMV TT . The developed vaccine‐induced antibodies that completely neutralized MERS‐CoV/EMC/2012 isolate 46 . Furthermore, we have shown that fusing RBM into AP205‐VLPs results in an effective vaccine candidate which induced RBD‐ and spike‐specific antibodies which were capable of neutralizing the wild‐type virus SARS‐CoV‐2/ABS/NL20 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Using this technique, we have recently developed a vaccine against MERS‐CoV by incorporating the RBM of MERS‐CoV into CuMV TT . The developed vaccine‐induced antibodies that completely neutralized MERS‐CoV/EMC/2012 isolate 46 . Furthermore, we have shown that fusing RBM into AP205‐VLPs results in an effective vaccine candidate which induced RBD‐ and spike‐specific antibodies which were capable of neutralizing the wild‐type virus SARS‐CoV‐2/ABS/NL20 35 .…”
Section: Discussionmentioning
confidence: 99%
“…VLPs also contain viral PAMPs, such as nucleic acids, that help activate, in many cases, and an adjuvant-free protective immune response ( Venter et al, 2011 ; Li M. et al, 2021 ; Ortega-Rivera et al, 2021 ; Royal et al, 2021 ; Warner and Frietze, 2021 ). Additionally, if they are made in bacteria, VLPs may contain some bacterial components that further promote a protective response without use of classical alum adjuvants ( Mohsen et al, 2021 , 2022 ). As OMVs are directly derived from bacteria, they display many PAMPs that VLPs do not contain, such as LPS, flagellin, and lipopeptides, and making them self-adjuvanting.…”
Section: Discussionmentioning
confidence: 99%
“…This effect, despite being T cell-independent, then leads to strong stimulation of B cells and induction of a robust and long-lasting antibody response ( Bachmann et al, 1993 ; Fries et al, 2021 ) that can even be achieved without the addition of synthetic adjuvants ( Zhang et al, 2000 ; Li Y. et al, 2021 ). Furthermore, VLPs naturally encapsulate bacterial nucleic acids when propagated in bacterial expression systems, which further activate antigen-presenting cells and B cells ( Mohsen et al, 2021 ). The success of the VLP platform has already resulted in many FDA-approved VLP-based vaccines, including Cervarix ® ( Harper et al, 2004 ) and Gardasil ® ( Villa et al, 2005 ) for Human Papilloma Virus (HPV), and Engerix ® ( Keating et al, 2003 ) and Recombivax ® ( Van Damme et al, 2009 ) for Hepatitis B Virus (HBV) (see Table 1 ).…”
Section: Virus-like Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CuMV TT -Ara h 1 was demonstrated to effectively treat peanut allergy in mice [17]. Another example of CuMV TT as an excellent vaccine delivery vehicle was against MERS coronavirus, which was potent to induce high titers of RBD-and spike protein-specific IgG antibodies, which could neutralize virus in vitro [18].…”
Section: Strainmentioning
confidence: 99%